Secure efficient signature for internet of things over near-ring. Issue 2 (July 2021) - Muthukumaran, V; Arun, M; Satheesh Kumar, S; Kumta, Samyukta D; Angeline Kavitha, M; Vijayaraghavan, R
Abstract: Prediction of air quality is a topic of great interest in air quality research due to direct With rapid progression in remote innovation and inescapable computerized innovation have given in expanding prevalence and enthusiasm of Internet of Things (IoT) procedure, universally giving comfort and knowledge to our day by day exercises. In IoT based framework situation, shrewd parts are associated wherever as all inclusive things connected in an inescapable model. Guaranteeing security for intersection among brilliant items is fundamentally progressively significant, in this paper, we propose a novel signature scheme which is utilized for carrying communication amongst devices in IoT environment. Moreover we revealed different scheme that are vulnerable. The significance of the proposed scheme over other existing scheme are analyzed in terms of the summary which is illustrated using performance and security comparison.